2022
DOI: 10.1177/13621688221111623
|View full text |Cite
|
Sign up to set email alerts
|

Classroom environment and willingness to communicate in English: The mediating role of emotions experienced by university students in China

Abstract: The present study examines the direct and indirect relationships between classroom environment (CE), L2 (second/foreign language) learner emotions (i.e. enjoyment, anxiety and boredom), and their willingness to communicate (WTC) in classes for English as a foreign language (EFL). Participants were 2,268 university students in China. Pearson correlation analyses showed significant correlations between CE, L2 emotions, and WTC, with effect sizes ranging from small to large. In addition, the three L2 emotions wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 58 publications
2
20
0
Order By: Relevance
“…Along the way, we established that FLE was negatively linked to both FLCA and FLB, which were positively correlated with each other. These patterns correspond to the ones uncovered in previous research on both WEIRD and non-WEIRD populations (Dewaele, Botes, et al, 2022; Dewaele, Albakistani, et al, 2022; Li, 2022; Li & Han, 2022; Li et al, 2022).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Along the way, we established that FLE was negatively linked to both FLCA and FLB, which were positively correlated with each other. These patterns correspond to the ones uncovered in previous research on both WEIRD and non-WEIRD populations (Dewaele, Botes, et al, 2022; Dewaele, Albakistani, et al, 2022; Li, 2022; Li & Han, 2022; Li et al, 2022).…”
Section: Discussionsupporting
confidence: 89%
“…FLE and FLB had no effect on FL performance, but FLCA had a significant negative effect. Using a mediation analysis to understand the direct and indirect effects of the classroom environment, FLE, FLCA, and FLB on WTC, Li et al (2022) collected data from 2,268 university EFL learners in China. The authors found that FLE was negatively related to both FLCA and FLB, which were positively correlated with each other (with small to medium effect sizes).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As indicated by Li et al. (2022), L2 grit can be closely associated with and predict its internal variable of L2 emotions, such as foreign language enjoyment and anxiety (e.g., Khajavy & Aghaee, 2022; Teimouri et al., 2020). It can be consistently found that L2 grittier learners will have a higher level of enjoyment and a relatively lower level of anxiety.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Student motivation, language apprehension, and self-efficacy are intrinsic factors that significantly influence their propensity to engage in English communication. Research (Darasawang & Reinders, 2021;Li et al, 2022;Mahmoodi & Moazam, 2014)has demonstrated a positive correlation between elevated levels of self-efficacy and intrinsic motivation and increased WTC. This correlation promotes a feeling of assurance and a greater propensity to participate in linguistic exchanges.…”
Section: Willingness To Communicate (Wtc) In Englishmentioning
confidence: 99%